A new species of Tafalisca Walker, 1869 from the Iguacu National Park, Brazil (Grylloidea, Eneopteridae, Tafaliscinae) - Dias, Pedro Guilherme B. S.; Mello, Francisco de Assis Ganeo de [UNESP] (Magnolia Press, 2010)
The aim of this work was to describe a new cricket species from the Iguacu National Park, Southeastern Brazil. We characterize the genitalia and external morphology of Tafalisca paranaensis n. sp. and the genitalia of Tafalisca paulista Rehn, 1918 providing a comparison between these species.
Keywords: Tafaliscini; cricket; Neotropical; Atlantic Forest; taxonomy